Spatial effects and endogeneity in a Ricardian model of climate change: an application to a Mediterranean region. Issue 3 (2nd July 2020) - Nicita, Lea; Cucuzza, Giuseppe; De Salvo, Maria; Prato, Carlo; Signorello, Giovanni
ABSTRACT: The relationship between land values, climate and landscape diversity is investigated for a region of the Mediterranean where climate impacts are expected to be particularly severe. The Ricardian approach is applied, and spatial correlation and endogenous selection of farm type are accounted for. The analysis is at the farm level, and it is completely geocoded. It is found that farmland value is affected by both climate and landscape agrobiodiversity, and that their impacts differ across models. However, landscape agrobiodiversity is extremely significant, and it greatly contributes to sustaining the mean level of land value. The results show that spatial correlation and the endogenous nature of adaptation substantially affect impacts assessment and suggest that spatial dependence and adaptation should not be overlooked in Ricardian models.